Engineering a 3D platform for testis bioengineering: generation and proteomic profiling of decellularized fish testicular scaffolds - Rosa, Ivana Felipe; Souza, Beatriz Marques; Doretto, Lucas Benites; Rodrigues, Maira da Silva; Barquilha, Caroline Nascimento; Fioretto, Matheus Naia; Frediani Portela, Luiz Marcos; Souza Vieira, José Carlos; Justulin, Luis Antonio; de Magalhães Padilha, Pedro; Shao, Changwei; Nóbrega, Rafael Henrique (Frontiers in Bioengineering and Biotechnology, 2025)
Decellularization represents a robust strategy for generating biologically derived scaffolds that retain the native architecture and biochemical complexity of the extracellular matrix (ECM), thereby providing a conducive microenvironment for germ cell adhesion, proliferation, and differentiation—processes fundamental to the reconstitution of testicular function. While decellularized ECM (dECM) scaffolds have been extensively utilized in mammalian organoid systems for in vitro spermatogenesis and fertility-related research, the development of standardized protocols tailored to teleost models remains largely unexplored. In the present study, we established an efficient decellularization protocol for testicular tissue derived from Astyanax lacustris, employing 0.1% sodium dodecyl sulfate (SDS) in conjunction with physical agitation. The efficacy of cellular removal was confirmed by DNA quantification, histological evaluation and DAPI staining, whereas the preservation of ECM integrity was validated through immunofluorescence, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and proteomic profiling. SDS treatment effectively eliminated cellular components while preserving key ECM proteins, including Collagen I, Fibronectin, and Laminin α1. Notably, critical ultrastructural features—such as the basal lamina, seminiferous tubules, and the D-periodic banding pattern of collagen fibrils—were retained post-decellularization. Proteomic analyses revealed enrichment of proteins associated with ECM organization, cell adhesion, and collagen biosynthesis, while proteins involved in glycolysis and metabolic pathways were downregulated. Moreover, the decellularized matrix retained a comprehensive repertoire of matrisome components, including multiple collagen subtypes (Col1, Col2, Col4, Col5, Col6, and Col7), glycoproteins (Fibronectin, Laminin), proteoglycans (Heparan sulfate), ECM-affiliated proteins (Integrins), secreted factors (Collagen- and calcium-binding EGF), and ECM regulators (Glycosaminoglycans). Collectively, these findings demonstrate that our protocol effectively preserves the structural and functional hallmarks of the testicular ECM, underscoring its potential as a biologically relevant scaffold for future applications in fish reproductive biology. Further investigations are warranted to optimize hydrogel formulations and assess their capacity to support the in vitro proliferation and differentiation of spermatogonial stem cells (SSCs).